Cylindrical Dielectric Resonator Antennas with Harmonic Control as an Active Antenna Radiator. (19th February 2009) - Lucci, L.; Manara, G.; Nepa, P.; Pelosi, G.; Selleri, S.
Abstract : A cylindrical dielectric resonator antenna is proposed as a radiator for an active integrated antenna. Harmonic tuning, which is the key step in designing active antenna radiators, is achieved via a combination of shape factor control over the resonator and insertion of reactive elements in the feed system. Numerical simulations are carried out in a finite elements framework and a layout for the complete antenna is proposed, aimed at compactness for subsequent utilization of the radiator as an element in an active array for satellite communications.